Taller Yuani y su influencia en el aprendizaje del área de Ciencia y Ambiente en los niños de tres años de la I. E. 224 Indoamérica – Víctor Larco Herrera, 2017 - Pozo Reyes, Anita Lucia (2018)
The present investigation has purpose determine the influence of the YUANI workshop in the learning of the area of Science and Environment in children of three years of the I.E. 224 Indoamerica - Victor Larco Herrera._x000D_ The type of research is applied, with quasi-experimental design with pre and posttest with experimental group and control group._x000D_ This research had as sample of study 40 students, being the experimental group the green classroom with 20 students and the control group of the pink classroom with 20 students._x000D_ The results obtained have affected the YUANI study and its influence on the learning of the Science and Environment area in the children of three years of EI. 224 Indoamerica - Victor Larco Herrera, the results showed that the students of the experimental group achieved improve their learning in the area of Science and Environment with 42.16% unlike the control group.